(untitled) (Bangladesh Journal of Zoology, 2018)
The current study was carried out to evaluate prevalence of endoparasites in freshwater fishes of Chenab River. The fish samples were collected from Chenab River during November 2014 to March 2015. In total, 285 fishes were examined for parasites, of which 75 fishes (26.1% of the total sample) were infected with parasites. Among the species, prevalence of infection was maximum in Rita rita (60%) and in Labeo rohita (37.5%). The minimum prevalence was, however, recorded in Oreochromis aureus (16.7%) and no parasite was found in Mastacembatus armatus. Among the organs, highest prevalence of endoparasites was observed in the intestine (43%) and gall bladder (33.2%). The prevalence of nematode and trematode was found higher (29 and 21%, respectively) in all fishes. It was revealed that the diversity of endoparasites in freshwater fishes is high. Since the use of fish as a ready source of food is increasing, therefore, the overall health status of fish in a system is becoming more valuable. Bangladesh J. Zool. 46(1): 53-61, 2018